Unconventional photonic gaps of a one dimensional photonic band gap structure - Ali, Munazza Zulfiqar (Oficyna Wydawnicza Politechniki Wrocławskiej, 2011)
We present a scheme to realize the zero–n gap and the zero–øeff gap in a one dimensional photonic band gap structure containing metamaterials. The electric permittivity and the magnetic permeability of the layers of the structure are represented by the Drude model and the resonant model. In a certain frequency range, the chosen structure behaves as a structure of alternate double negative and double positive layers to exhibit a zero–n gap. In another frequency range, it behaves as a structure of alternate permittivity negative and permeability negative layers to exhibit a zero–øeff gap. Some properties and benefits of having the zero–n and the zero–øeff gap in the same physical system are discussed.
Optica Applicata, Vol. 41, 2011, Nr 3, s. 743-752
Keywords: optyka; photonic band gap structures; metamaterials; zero–n gap; zero–øeff gap